Les Zkara du Maroc: savoirs, croyances et pouvoirs, de l'orientalisme au développement - Planeix, Ariel (Université de Paris I-Panthéon Sorbonne, 2013)
Keywords: Zkaras -- Maroc

Femme et famille en Tunisie : entre conservatisme et modernité - Bassalah, Safa (Faculté des sciences humaines et sociales de Tunis, 2013)
Keywords: Emigration -- Djerba -- Tunis

إسهامات علماء الإباضية في التفسير و علوم القرآن في القرنين الثالث عشر و الرابع عشر الهجريين دراسة تحليلية - المنذر, محمد سعيد (جامعة أم درمان الاسلامية, 2013)
Keywords: Coran -- Commentaires -- 9e siècle

الوقف الثقافِي للمغاربةِ في مصر العثمانيةِ من خلال سجلات المحاكم الشرعيّة تجربة أهل جربة وأهل فاس في القرن 12هـ/18م - مصلح, أحمد بن مهني (جامعة ﻣﺤمد اﻟﺨامس, 2013)
Keywords: Waqf (fondations) -- Djerba

حاشية سليمان الجربي على مختصر التفتازاني للسيخ سليمان بن عبد الحمن بن سليمان المغربي الجربي السمومني الشهير بسليمان الجربي (و 885هـ/1480م - ت 966هـ/1558م) دراسة وتحقيق - حاج أمحمد, يحيى بن بهون (جامعة الجزائر, 2013)

المشرق العربي من خلال جريدة الأمة لأبي اليقظان 1352-1357هـ/1933-1938م - الرزقي, خيري (جامعة الجزائر 2, 2013)

خصوصيات العمران الصحراوي - دراسة حالة مدينة غرداية - الأغواطي, محمد عبد الوهاب (جامعة عمار ثليجي, 2013)
Keywords: Urbanisme -- Mzab

مسائل التحقيقية في بيان التحفة الأجرومية للشيخ امحمد بن يوسف اطفيش تحقيق ودراسة - حيدرة, رشيد (جامعة السانيا, 2013)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914)

دور المجتمع المدني في تجسيد الحكم الراشد بولاية غرداية - باعلي وسعيد, باحمد بن صالح (جامعة الجزائر 3, 2013)

الحياة الاجتماعية والثقافية بوارجلان ونواحيها خلال القرنين 5-6هـ/11-12م - حمامد, محمد (جامعة أحمد دراية, 2013)

ملحق السير الشماخي من رجال 950هـ إلى رجال1350 هـ لمؤلفه أبي اليقظان إبراهيم دراسة وتحقيق: القسم الخاص بأعلام القرنين العاشر والحادي عشر الهجريين / السادس عشر والسابع عشر الميلاديين - كروشي, نور الدين (جامعة قسنطينة 2, 2013)
Keywords: Prosopographie -- Afrique du Nord

النظام الإداري في عمان خلال الفترة من القرن 6هـ/12م- 10هـ/16م - الخروصي, عبد العزيز بن هلال (جامعة الجزائر 2, 2013)

التنافس الدولي على مضيق هرمز وأثره على سيادة سلطنة عمان - الحجري, عامر بن محمد بن شامس (جامعة لاهاي, 2013)
Keywords: Politique étrangère -- Oman

أبو العباس أحمد بن سعيد الشماخي وآراؤه الأصولية - مصباح, عيسى بن باحمد (جامعة الجزائر, 2013)
Keywords: Foi -- Traité

A Grammar of Awjila Berber (Libya) based on Umberto Paradisi’s Material - Van Putten, Marijn (Leiden University, 2013)
Keywords: Linguistique -- Djebel Nefousa

イバード派イスラーム思想における共同体論の研究 - Kondo, Yohei (The University of Tokyo, 2013)

أبو اليقظان ودوره في الحركة الاصلاحية في الجزائر (1888-1973) - ربيعة, ناصر (جامعة محمد خيضر, 2013)
Keywords: Réformisme -- Mzab

مسائل علم الكلام عند الإباضية عمرو خليفة النامي أنموذجا - نجار, أبو اليقظان; شعلان, ياسين (جامعة الأمير عبد القادر, 2013)

‏منهج الشيخ بيوض في الاجتهاد الفقهي - فخار, جابر بن سليمان (جامعة الجزائر, 2013)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981); Fiqh; Fiqh -- Mzab -- 20e siècle; Ijtihad -- Mzab -- 20e siècle

‏محمد بن عمر ابن أبي ستة المشهور بالمحشي حياته والآثاره - بن يحياتن, خالد ‏بن يوسف (‏معهد العلوم الشرعية, 2013)

From Siraf to Sumatra: Seafaring and Spices in the Islamicate Indo-Pacific, Ninth-Eleventh Centuries C.E. - Averbuch, Brian (Harvard University, 2013)
Keywords: Zanzibar

Tārīkh al-siyāsī wa’l-ḥaḍārī li-Jazīrat Jarba mundh al-fatḥ al-islāmī ḥatā suqūṭ al-dawla al-ḥafṣiyya - Manshāwī, Muḥammad Maḥmūd (Jāmiʿat al-Fayyūm, 2013)

‏متاحف الفنون والعادات الشعبية بجزيرة جربة: متحف جربة للتراث التقليدي الحوافر والحدود الأفق - ثابت, علي (Institut Supérieur des Sciences Culturelles et Métiers du Patrimoine, 2013)
Keywords: Musée -- Djerba

فقه الإمام أبي عبدالله محمد بن محبوب العماني (ت:260هـ) : جمع وترتيب ودراسة - الحوسني, شمسة بنت عبد الله (جامعة القاهرة, 2013)
Keywords: Fiqh

الدرجيني و منهجه في كتاب طبقات المشائخ بالمغرب - الريامي, علي بن سعيد (‏الجامعة الأردنية, 2013)
Keywords: Prosopographie -- Afrique du Nord

القبيلة ودورها في الحياة السياسية في عمان (1219 هـ / 1804 - 1305 هـ / 1888 م) - السعدي, ناصر بن سيف (جامعة السلطان قابوس, 2013)

الفكر السياسي عند الإمام السالمي :‏ ‏دراسة تحليلية - الريامي, عبد الله بن سليمان (الجامعة الإسلامية العالمية, 2013)

The Problems Encounter Teachers in Teaching Translation: Case Study Nafousa Mountain University Libya - Hammad, Suad Arebi (جامعة أم درمان الاسلامية, 2013)
Keywords: Linguistique -- Djebel Nefousa

جهود المفسرين في الرد على الخوارج - الحسيني, عمر بن مبيريك بن حذيفة (الجامعة الإسلامية بالمدينة المنورة, 2013)
Keywords: Kharijisme

إجراءات الإثبات بالشهادة في المعاملات المدنية والتجارية من منظور القانون العماني والفقه الإباضي - التوبي, يزن بن سيف بن محمد (جامعة السلطان قابوس, 2013)

Antécédent et conséquences du capital marque d’une destination sur les réponses attitudinales et comportementales des touristes cas de l’île de Djerba - Ben Hariz, Atef (Institut supérieure de gestion, 2013)
Keywords: Tourisme -- Djerba

Diagnostic pour l’identification de stratégies de pérennisation des oliviers millénaires de Djerba, Tunisie - Wehbe, N. (Université libanaise, 2013)
Keywords: Agriculture -- Djerba

Tower-Fortresses of Ancient Magan: A study of the tower-fortresses of the third millenium on the Oman Peninsula - Botan, Sam A. (Leiden University, 2013)
The tower-fortress on the Oman Peninsula have always been a mystery to archeologists. A total of 15 tower-houses have been excavated or surveyed by archeologists in the past decades and yet their purpose inside the settlements is still poorly understood. This thesis analyzes and evaluates the existing theories about the tower-houses and offers an alternative theory by taking into account the locations, sizes and construction techniques of these buildings, using the survey and excavation rapports. The origins of the tower-fortresses can be found as early as the end of the fourth millennium B.C., when the settlement pattern on the Oman Peninsula shifts from the coast to the hinterland. The shift from the coast to the oasis brought a diversification of resources as well as a tighter appropriation of space. Combined with an increase in the copper trade at the beginning of the third millennium, this induced more complexity in the social system. The form of social organization which emerged on the Oman Peninsula due to these factors, was one which was in a liminal stage between a chiefdom and a state society, called a stratified non-state society. The tower-fortress of the Oman Peninsula functioned in such a society as dwellings and locus of regional power of a particular family or moiety. The few towers that have been excavated show many similarities, such as: he positioning of the towers within the settlements, the usage of a platform on which the towers rest, the interior of the platform consisting of two rows of chambers divided by a corridor or well, the ditches surrounding the towers and thus separating them from the rest of the settlement, the fact that all of the towers could only have been accessed by a ramp, etc. All of these similarities indicate specialization and one has to wonder if the possibility exists of a specialized class of tower-builders, travelling from settlement to settlement
Keywords: Archéologie -- Oman

Similitudes et différences dans l’architecture vernaculaire domestique et religieuse d’un même groupement humain (Les berbères) dans deux contextes géographiques différents. (Cas de l’architecture vernaculaire de l’ile de Djerba et les montagnes de Matmata, Demmer et Nafousa en Libye) - Ben Younes, Houda (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2013)
Keywords: Architecture -- Djerba

Habitat semi-collectif à Midoun Djerba - Belhassine, Ridha (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2013)
Keywords: Architecture -- Djerba

Etude d’un cas d’aménagement touristique, zone de Cheikh Yahia-Sidi Jmour, île de Djerba - Keskes, Dhouha (Facultés Des Sciences de Tunis, 2013)
Keywords: Tourisme -- Djerba

Jespersen’s Cycle in Libyan Arabic and Nafusi Berber - Ghadghoud, Khawla (University of Manchester, 2013)
Keywords: Linguistique -- Djebel Nefousa

La valorisation du patrimoine immatériel juif de Djerba - Hammi, Yosr (Institut Supérieur des Métiers du Patrimoine de Tunis, 2013)
Keywords: Architecture -- Djerba

Etude de la commune de Guellala à Djerba (Tunisie) : une des dernières localités berbères - Hadjam, Aoussia (Université Paris 8, 2013)
Keywords: Linguistique

Le culte de la Maâmoura dans l’île de Djerba - Boukamcha, Souhaiel (Institut Supérieur des Métiers du Patrimoine de Tunis, 2013)
Keywords: Croyances populaires -- Djerba

Contribution des SIG à la gestion intégrée des ressources en eaux dans la région de Djerba - Ben Maiz, Amir (Faculté des Sciences Mathématiques, Physiques et Naturelles de Tunis, 2013)

Obésité morbide chez les enfants d’Age scolaire dans la région de Djerba. Etude de la prévalence et des facteurs de Risque - Selmi, Ines (Faculté de Médecine de Tunis, 2013)
Keywords: Médecine -- Djerba